Variation analysis of three Banyumas local salak cultivars (Salacca zalacca) based on leaf anatomy and genetic diversity - WIWIK HERAWATI; ADI AMURWANTO; ZUHROTUN NAFI’AH; ARDIANTI MAYA NINGRUM; SITI SAMIYARSIH (Biodiversitas Journal of Biological Diversity, 2018)
Herawati W, Amurwanto A, Nafi’ah Z, Ningrum AM, Samiyarsih S. 2018. Variation analysis of three Banyumas local salak cultivars (Salacca zalacca) based on leaf anatomy and genetic diversity. Biodiversitas 19: 119-125. A variation analysis of three salak cultivars was conducted in Banyumas District, Central Java, Indonesia. The aim of the study was to investigate variation amongst the cultivars based on anatomy and genetic diversity by using RAPD (Random Amplified Polymorphic DNA) technique. The result of the study showed that all salak cultivars have similar variation in leaf anatomy. The only distinguishing characteristic is the number of trichomes on cultivars Kedung Paruk and Kalisube per 1 mm2 unit of leaf area, while the cultivars of Candinegara lacked trichomes. Ten primers could detect 50 polymorphic bands (80,6%) from a total of 62 bands which could be observed clearly. The percentage of polymorphic loci in 'Candinegara' was 64%, 'Kedung Paruk' 62%, and 'Kalisube' 44%. The heterozygosity value of 'Candinegara' was 0.1590, 'Kedung Paruk' 0,1449, and 'Candinegara' (0.0235). Meanwhile, the furthest genetic distance was shown by 'Kedung Paruk' and ‘Candinegara’ (0.0704). This result gives us important basic information about cultivars of Salacca zalacca in Banyumas District which have high genetic diversity and germplasm. These results can be used for further research such as for conservation and genetic engineering.